2018
DOI: 10.3389/fnagi.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Biomarkers of mTOR Inhibition on Vascular and Metabolic Functions in Aging Brain and Alzheimer’s Disease

Abstract: The mechanistic target of rapamycin (mTOR) is a nutrient sensor of eukaryotic cells. Inhibition of mechanistic mTOR signaling can increase life and health span in various species via interventions that include rapamycin and caloric restriction (CR). In the central nervous system, mTOR inhibition demonstrates neuroprotective patterns in aging and Alzheimer’s disease (AD) by preserving mitochondrial function and reducing amyloid beta retention. However, the effects of mTOR inhibition for in vivo brain physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…It is well documented that TBI increases the risk for developing dementia, such as Alzheimer’s disease (AD) later in life Mortimer et al, 1991 ; Gavett et al, 2010 ; Lee et al, 2013 ; ( Barnes et al, 2016 ). Protecting brain vascular and metabolic functions ( Hammond et al, 2020 ; Hammond et al, 2021 ; Hammond and Lin, 2022 ) is critical to slowing down brain aging ( Hoffman et al, 2017 ) and mitigating the risk for AD ( Lee et al, 2018 ; Lin et al, 2020 ), as these functions serve an essential role in sustaining essential brain activities ( Lin et al, 2008 ; Lin et al, 2010 ). It is also consistent with our previous findings that inulin is protective of systemic metabolism and reduces the risk for AD in a mouse model with human APOE4 alleles, the strongest genetic risk factor for AD ( Hoffman et al, 2019 ; Yanckello et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that TBI increases the risk for developing dementia, such as Alzheimer’s disease (AD) later in life Mortimer et al, 1991 ; Gavett et al, 2010 ; Lee et al, 2013 ; ( Barnes et al, 2016 ). Protecting brain vascular and metabolic functions ( Hammond et al, 2020 ; Hammond et al, 2021 ; Hammond and Lin, 2022 ) is critical to slowing down brain aging ( Hoffman et al, 2017 ) and mitigating the risk for AD ( Lee et al, 2018 ; Lin et al, 2020 ), as these functions serve an essential role in sustaining essential brain activities ( Lin et al, 2008 ; Lin et al, 2010 ). It is also consistent with our previous findings that inulin is protective of systemic metabolism and reduces the risk for AD in a mouse model with human APOE4 alleles, the strongest genetic risk factor for AD ( Hoffman et al, 2019 ; Yanckello et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin (sirolimus) enhances autophagy via the direct binding to mTOR and FKBP12, leading to the inhibition of mTORC1, and is the most studied agent in preclinical models of AD. Rapamycin was demonstrated to enhance Aβ degradation and to reduce plaque burden, to decrease the number of tau tangles, to ameliorate neuro‐inflammation, to restore brain vascular and metabolic functions and to reverse cognitive deficits in numerous in vitro and in vivo AD settings (Lee, Yanckello, et al, ; Pierzynowska et al, ). Other agents that inhibit mTORC1 in a manner similar to rapamycin (rapalogs) also displayed protective properties in the context of AD; For example, temsirolimus promoted clearance of amyloid‐β and provided protective effects in cellular and animal models of AD (Jiang et al, ); and administration of everolimus restored cognitive function and mood in a murine model of AD (Cassano et al, ).…”
Section: Autophagy Inducers As a Therapeutic Approach In Ad: An Overvmentioning
confidence: 99%
“…Justice et al [ 72 ] showed a similar result in healthy older subjects as time to complete TMT-B was improved by 18% and 14% in response to supplementation with high and low doses of sodium nitrite for 10 weeks, respectively. Potential mechanisms explaining the cognitive effects could include a CR-induced Akt phosphorylation through the insulin-PI3K-Akt signalling pathway [ 73 , 74 ], increased NO production, and potentiation of pre-synaptic neurotransmission [ 75 , 76 ] occurring alongside an enhancement of neurovascular and metabolic coupling [ 77 ].…”
Section: Discussionmentioning
confidence: 99%